A significant excess in major merger rate for AGNs with the highest eddington ratios at z < 0.2 - Marian, Victor; Jahnke, Knud; Andika, Irham Taufik; Bañados Torres, Eduardo; Bennert, Vardha N.; Cohen, Seth; Husemann, Bernd; Kaasinen, Melanie; Koekemoer, Anton M.; Mechtley, Mira; Onoue, Masafusa; Schindler, Jan-Torge; et al. (The astrophysical journal, 2020)
Observational studies are increasingly finding evidence against major mergers being the dominant mechanism responsible for triggering an active galactic nucleus (AGN). After studying the connection between major mergers and AGNs with the highest Eddington ratios at z = 2, we here expand our analysis to , exploring the same AGN parameter space. Using ESO VLT/FORS2 , , and color images, we examine the morphologies of 17 galaxies hosting AGNs with Eddington ratios , and 25 mass- and redshift-matched control galaxies. To match the appearance of the two samples, we add synthetic point sources to the inactive comparison galaxies. The combined sample of AGN and inactive galaxies was independently ranked by 19 experts with respect to the degree of morphological distortion. We combine the resulting individual rankings into multiple overall rankings, from which we derive the respective major merger fractions of the two samples. With a best estimate of f m,agn = 0.41 ± 0.12 for the AGN host galaxies and f m,ina = 0.08 ± 0.06 for the inactive galaxies, our results imply that our AGN host galaxies have a significantly higher merger rate, regardless of the observed wavelength or applied methodology. We conclude that although major mergers are an essential mechanism to trigger local high Eddington ratio AGNs at , the origin of of this specific AGN subpopulation still remains unclear.